UNSAFE SEXUAL BEHAVIOUR AMONG HIV-POSITIVE MSM PARTICIPATING IN COMMUNITY-BASED TREATMENT ADHERENCE PEER SUPPORT PROGRAM - Jaafar, Safirah Jaan; Awang Lukman, Khamisah; Safian, Nazarudin; Myint , Than; Swe; Hassan, Mohd Rohaizat; Sutan, Rosnah; Chin Mun , Wong; Jeffree, Mohammad Saffree (Malaysian Journal of Public Health Medicine, 2021)
This study aims to investigate the unsafe sexual behaviour among HIV-positive men who have sex with men (MSM) participating in community-based Treatment Adherence Peer Support Program (TAPS) based in Kota Kinabalu, Sabah. A cross-sectional study that involved 109 HIV-positive MSM was conducted using a validated questionnaire adapted from Integrated Biological and Behavioural Surveillance (IBBS) 2012, in two main languages which are Malay and English.1 This questionnaire contained information on socio-demographic factors, respondents’ sexual history since they were diagnosed with HIV, and participation with community-based TAPS. Among the total 109 respondents, 62.4% had stated that they had practised unsafe sexual behaviour since they were diagnosed with HIV. Prevalence of self-reported Sexually Transmitted Infections (STIs) was 24.8%. About 92.7% of participants were on highly active antiretroviral therapy (HAART) and had achieved 96% of compliancy. Prevalence of unsafe sexual behaviour differed significantly between respondents on HAART (66.3%) compared to the non-HAART group (12.5%) (?2 = 7.005, p < 0.01). Duration of last participation in the TAPS program significantly associated with unsafe sexual behaviour (?2 = 16.96, p <0.01). There is a high prevalence of unsafe sexual behaviour and self-reported STIs among HIV-infected MSM. Participation in TAPS resulted in a higher percentage of HAART coverage and the compliancy among the respondents; however, the prevalence of unsafe sexual behavioural remains high. The study findings highlight the importance of regular STIs screening among HIV-infected MSM.